Indicadores cientométricos normalizados: um estudo na produção científica brasileira internacional (1996 a 2011) - Grácio, Maria Cláudia Cabrini [UNESP]; Oliveira, Ely Francina Tannuri de [UNESP] (Escola de Ciência da Informação da UFMG, 2014)
In this research, we aim at comparatively analyzing the normalized scientometric indicators of production and citation of the Brazilian research, in the 27 areas of knowledge, from the data presented in the Scimago Journal & Country Rank gate, in the period between 1996 and 2011. Besides, we aim at assessing the correlation among these indicators in order to verify if the insertion and the impact are associated within the Brazilian performance. Eventually, we aim at grouping the areas by means of the similarities of the indicators analyzed. As our procedure, we calculated the percentage of Brazilian journals, from the Journal Rankings option, and the normalized Brazilian index for the indicators under analysis, from the Country Rankings option. Next, we calculated the Pearson correlations among the indicators and we achieved the cluster analysis, in order to group the 27 areas, according to their similarities in the indicators. As results, Brazil ranks above average among the producing countries, in all the normalized indexes. Except from the citation average, all the other indicators present positive correlations. 4 clusters were constituted for the Brazilian performance. The results show that the grouped and articulated analysis of normalized indexes enables a more consistent view of the Brazilian science

Nesta pesquisa, objetiva-se: analisar comparativamente os indicadores cientométricos normalizados de produção e de citação da pesquisa brasileira, nas 27 áreas do conhecimento, a partir dos dados apresentados no portal SCImago Journal & Country Rank, no período de 1996 a 2011; avaliar a correlação entre esses indicadores, a fim de se verificar se a inserção e o impacto apresentam-se associados no desempenho brasileiro; e agrupar as áreas por meio das similaridades dos indicadores analisados. Como procedimento, para cada área, calcularam-se a porcentagem de periódicos brasileiros, a partir da opção Journal Rankings, e o índice normalizado brasileiro para os indicadores em análise, a partir da opção Country Rankings. A seguir, calcularam-se as correlações de Pearson entre os indicadores e realizou-se a análise de cluster, a fim de se agrupar as 27 áreas em função das similaridades nos indicadores. Como resultados, constatou-se que o Brasil ocupa posição acima da média dos países produtores, para todos os índices normalizados. Com exceção da média de citação, todos os demais indicadores apresentam correlações positivas. Constituíram-se quatroclusters para a atuação brasileira. Os resultados apontam que a análise conjunta e articulada dos índices normalizados possibilita uma visualização mais consistente da ciência brasileira.
International Brazilian scientific production: a scientometric study by normalized indicators (1996-2011)
Keywords: Indicadores cientométricos normalizados; Produção científica brasileira; Internacionalização da pesquisa brasileira; Normalized scientometric indicators; Brazilian scientific production; Internationalization of Brazilian research